AB0705 Psychopathologic Involvement in Systemic Sclerosis: A Pilot Study. (9th June 2015) - Meijs, J.; Ercan, E.; Baptist, E.; van der Wee, N.; Tritanon, O.; van Buchem, M.; Huizinga, T.; Schouffoer, A.; Middelkoop, H.; de Vries-Bouwstra, J.
Abstract : Background: Involvement of the brain in systemic sclerosis (SSc) could be suspected given the presence of disturbances on cerebrovascular imaging or mental dysfunction, including disorders of cognition or mood. It is important to confirm this since the intervention of first choice for cognitive disorders is highly depending on the pathophysiology. Objectives: To investigate whether mental complaints in patients with SSc are related to organic brain dysfunction. Methods: Twenty SSc patients with self-reported mental complaints, including concentration problems, fatigue, memory loss, or depression, were cross-sectionally assessed by neuropsychological testing, psychiatric evaluation and magnetic resonance imaging (MRI) of the brain. All patients completed the Hospital Anxiety and Depression Scale, Dissociation Experience Scale, a screenings tool for fatigue (MFI-20), Short Form-36 and Neuropsychiatric Inventory. Patients were compared with 20 age and sex matched healthy controls. Results: Patients and healthy controls did not differ with respect to sociodemographic characteristics. In 5 SSc patients cognitive dysfunction was considered questionable by the neuropsychologist. Patients performed slightly worse on cognition tasks as compared to healthy controls, but all test results were within the normal range. The MRI showed small white matter hyperintensities (WMH) in 18 patients and in 15 healthy controls. The neuropsychological tests were completely normal within those 15 healthy controls. Thirteen SSc patients with WMH on MRI, had normal neuropsychological tests and no mood disorder. Four patients with WMH had a mood disorder. Conclusions: Based on this pilot study, SSc patients show slight disturbances of mental functioning as compared to healthy controls, but their performance is within the normal range. No clear association between mental dysfunction and organic brain abnormalities could be detected. In case of mental dysfunctioning in SSc patients, we propose psychological intervention, starting with psychoeducation and in some cases cognitive-behavioural therapy, is the best treatment. Disclosure of Interest: J. Meijs Grant/research support from: Jessica Meijs was supported by an unrestricted educational grant of Actelion Pharmaceuticals Nederland BV (Woerden, The Netherlands)., E. Ercan: None declared, E. Baptist: None declared, N. van der Wee: None declared, O. Tritanon: None declared, M. van Buchem: None declared, T. Huizinga: None declared, A. Schouffoer: None declared, H. Middelkoop: None declared, J. de Vries-Bouwstra: None declared